Edgeless porous carbon coating for durable and powerful lead-carbon batteries - Wee, Jae-Hyung; Nomura, Keita; Nishihara, Hirotomo; Kim, Doo-Won; Hong, Seungki; Choi, Go Bong; Yeo, Sang Young; Kim, Jin Hee; Jung, Ho-Young; Kim, Yoong Ahm (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
A systematic study considering the microstructural effect of carbon materials on the electrochemical or electrocatalytic performance is essential for developing carbon electrode materials of electric vehicles and smart grids that require durable and robust energy supply. In this study, the edge sites within activated carbons (ACs) were physically modified via thermal treatment to clarify the relationship between the edge density and hydrogen evolution reaction (HER). Moreover, their dominant contribution to the electrochemical performance of lead-carbon batteries was demonstrated. The ACs exhibited decreased defect density and enhanced crystallinity due to the merger of micro-domains during a high-temperature thermal treatment (HTT). In contrast to the specific surface area, the edge area of the ACs, which was quantified via temperature programmed desorption up to 1800 degrees C, decreased significantly with increasing HTT temperature. We have confirmed a close relationship between the edge densities and HER parameters. The lead-carbon battery unit cell employing HTT1600 with the lowest edge ratio (0.81%) exhibited a higher charging efficiency, higher cycling stability, and lower water loss than the cell employing pristine AC with a high edge ratio (8.42%). The edge ratio of carbon materials can be considered an important parameter in designing electrode materials for electrochemical energy storage. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: TEMPERATURE-PROGRAMMED DESORPTION; NEGATIVE ACTIVE MATERIAL; ACID-BATTERIES; GRAPHENE EDGES; HEAT-TREATMENT; PERFORMANCE; EVOLUTION; ADDITIVES; ELECTRODE; ORIGIN